P582 Vedolizumab: Effects on liver function in an IBD and IBD/PSC cohort. (16th January 2018) - Doherty, J; Buckley, M; Cullen, G; Horgan, G; Mulcahy, H; Doherty, G; Sheridan, J
Abstract: Background: Primary sclerosing cholangitis (PSC) is a disease characterised by inflammation and destruction of the hepatic bile ducts often associated with inflammatory bowel disease (IBD). Vedolizumab is a gut-selective antibody for the treatment of ulcerative colitis (UC) and Crohn's disease (CD). We sought to look at the effects of vedolizumab therapy on liver biochemistry in patients with IBD and IBD and co-existing PSC. Methods: We conducted a retrospective study of all patients at SVUH treated with vedolizumab. Basic demographics, markers of response to therapy, alongside phenotypes of IBD and PSC were collected. Liver biochemistry was analysed at 0, 2, 8, 12, 24, and 36 weeks. Results: A total of 46 patients were treated with vedolizumab (13 CD, 31 UC, and 2 IBD-U). Median age was 37.5 years (17–70). Two patients were excluded due to no available bloodwork. 70.5% ( n − 31) were treated with vedolizumab for IBD alone. 29.5% ( n = 13) had a concurrent diagnosis of PSC. 68.9% of patients were still on vedolizumab at the time of the review. Ten patients were post liver transplant. The median alkaline phosphatase (ALP) level at 0 weeks for the IBD cohort was 69 vs. 126 in the IBD/PSC cohort. Median levels of ALP at 36 weeks in the IBD cohort was 78 vs. 190 in the IBD/PSC cohort. The IBD alone cohort showed no statistical change in ALP at any time over 36 weeks. In our IBD/PSC cohort, there was a statistically significant rise in ALP levels at 8, 12, 24, and 36 weeks when compared with levels at Week 0 ( p -values 0.019, 0.045, 0.005, and 0.028, respectively). On review of markers of response to therapy we saw an overall improvement in these at 6 months. Median CRP, albumin and faecal calprotectin levels (FCP) in both cohorts were down trending at 6 months after commencing vedolizumab. Conclusions: Vedolizumab therapy has no effect on liver biochemistry in patients with IBD alone. However, in individuals with PSC, serum ALP increased significantly while on vedolizumab therapy. Further work is warranted to investigate if this is due to the natural history of the disease or the effect of vedolizumab therapy.